A structural equation modeling of supply chain strategies for artemisinin-based combination therapies in Ugand - Nagitta, Oluka Pross; Mkansi, Marcia; Nyesiga, Sylvia Desire; Kajjumba, George William (Medicine Access, 2021)
Malaria is a killer disease in the tropical environment; artemisinin-based combination therapies (ACTs) play a central role in treating malaria. Thus, the supply and presence of ACT drugs in hospitals are a key feature in the fight against malaria. Supply chain management literature has focused on the private sector, and less attention has been paid to the public sector, especially hospitals. Aim: This study uses an interdisciplinary lens in investigating how to boost the supply and distribution of ACTs to save lives in low-income countries, specifically in Uganda. Methodology: The study adopted a quantitative research design using a questionnaire as the data collection instrument. Of the 440-population size, 304 of the sample population participated in the study. The model was estimated using structural equation modeling (SEM) to establish the causal relationship among the variables. Results: From the SEM analysis, all the hypotheses were significant at p<0.05. The availability of ACTs is strongly affected by strategic dimensions (0.612), followed by operation dimensions (0.257); strategic determinants significantly affect operational determinants by a magnitude of 0.599. The indirect influence of the strategic determinants via operational determinants on the availability of ACTs is not significant. Overall, the factors explained 63.9% of the observed variance in the availability of ACTs, and the ACT availability can be predicted as follows: ACT availability=0.612×strategic determinants+0.256×operation determinants. Top management commitment and organizational responsiveness are among the items that positively affect the availability of ACTs. Conclusion: Strategically, hospital management should invest in cheap technology and software to minimize the unavailability of medicines. Our research suggests that strategic and operational determinants should be integrated into the hospitals’ core business and implemented by the top management. The article contributes to theoretical and policy direction in the public sector medicine supply chain, specifically in public hospitals.
Keywords: Malaria; Supply chain coordination; Mutual understanding; Top management; Public health